Isolation and Extraction of as Ferulic Acid from Medicinally Active Andrographis Paniculata Plant and Synthesis of its Analogues (International Journal of Scientific Research in Science and Technology, 2025)
Ferulic acid has been shown to have biological activities such as antimicrobial, antioxidant, anti-inflammatory, anti-thrombogenic and anticancer properties. Moreover, it decreases liver and serum cholesterol, increases sperm viability, and all of these advantages are advantageous for coronary heart disease. Apart from this, it exhibits great commercial potential in the food, health and cosmetic industries. Because ferulic acid is absorbed and metabolized by the human body, it has additional advantages. Thus, devised a plan to extract and isolate ferulic acid from Andrographis Paniculata based on the aforementioned features. Based on the properties of this, we have strategies to isolate the ferulic acid and synthesis of their analogues like ester and amide. Which were characterized by 1HNMR and GCMS.